Need analysis of English subject for science program in senior high school grade XI - Rodiana, Mila; Sukarni, Semi (Jurnal Pendidikan Surya Edukasi (JPSE), 2023)
The focus of this need analysis is on the students in Senior High School (SMA) Grade XII in Wonosobo specifically in English subject. The main objective is to know how deeply they understand the English material in the class. Students in this level (grade twelve) should have skills both speaking and writing higher than students in junior or elementary. At least they know how to communicate using simple words and understand the main topic in reading or grammar in writing. Hence, this study aims to describe the learners’ target need to learn English in science programs at Senior High Schools and to identify English skills needed by students in science programs. There were 22 twelfth graders involved in this study which consisted of students of SMA 1 Wonosobo. To obtain the data, a questionnaire in Google form was used. The findings showed that 86,4% of students like English as a subject, while 13,6% of students do not like English as a subject. Further, the interest in English from the students is also important. Students need a deep understanding of the material related to the terms. Another necessity is the English skills for their provision of knowledge to continue their study.